3D‐Printed Acoustofluidic Devices for Raman Spectroscopy of Cells. Issue 10 (21st October 2021) - Santos, Harrisson D. A.; Silva, Amanda E.; Silva, Giclênio C.; Lima, Everton B.; Marques, Alisson S.; Alexandre-Moreira, Magna S.; Queiroz, Aline C.; Jacinto, Carlos; Henrique Lopes, J.; Rocha, Uéslen; Silva, Glauber T.
Abstract : Acoustofluidics leads to innovative methods for cellular levitation that can help Raman biospectroscopy avoid spurious substrate signals while keeping cells alive within a controlled microenvironment. In article number 2100552, Harrisson D. A. Santos, Uéslen Rocha, Glauber T. Silva and co‐workers present a 3D‐printed acoustofluidic device that allows single‐cell Raman analysis with preferred quality over ordinary strategies.